Agro-morphological characterization and diversity assessment of advanced breeding lines of spring rice in the plains of eastern Nepal - Bhusal, Babita; Bhattarai, Bandana; Badu, Ramita; Yadav, Ajay Kumar; Loniya, Shiv Shankar; Sapkota, Manoj; Gyawali , Anisha; Timilsina , Sandip; Ayer, Dipendra Kumar (Journal of Agriculture and Natural Resources, 2023)
Agro-morphological characterization and genetic diversity analysis is pivotal to identify elite genes for further improvement of germplasms. In Spring 2022, 52 spring (Chaite) rice accessions were evaluated for 12 agro-morphological traits in alpha lattice design with two replications under irrigated condition at agronomic farm of Gauradaha Agriculture Campus, Jhapa, Nepal. Results showed the existence of considerable amount of diversity in rice accessions. The first three principal components (PC1, PC2 and PC3) with eigen value greater than one were identified with a total cumulative variation of 95.04% showing that the accessions could be grouped at least into three main varied classes. The accessions were grouped into 5 clusters. The accessions falling in cluster II had the maximum grain yield. The accessions namely Hardinath-1 (4.87 t/ha), IR17A3019 (4.37 t/ha), IR17A2949 (4.12 t/ha) were found to have high yielding accessions. High genetic variability among the rice accessions was found for the traits viz., grain yield, thousand grain weight, length breadth ratio, days to flowering, days to maturity, panicle length, effective tiller per hill and have pertinency in future spring rice breeding programs for the selecting potential parent lines based on those traits.